2018
DOI: 10.1002/ajb2.1021
|View full text |Cite
|
Sign up to set email alerts
|

Differential growth of pavement cells of Arabidopsis thaliana leaf epidermis as revealed by microbead labeling

Abstract: Growth of the anticlinal and outer periclinal walls of leaf pavement cells is heterogeneous. The growth of the lobes resembles cell elongation via diffuse growth rather than tip growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…6D, S5D-F) presumably restricting further widening of lobes while promoting anisotropic expansion in length of lobes. These observations and predictions are consistent with anisotropic growth patterns in pavement cells reported by Elsner et al (2018).…”
Section: Discussionsupporting
confidence: 91%
“…6D, S5D-F) presumably restricting further widening of lobes while promoting anisotropic expansion in length of lobes. These observations and predictions are consistent with anisotropic growth patterns in pavement cells reported by Elsner et al (2018).…”
Section: Discussionsupporting
confidence: 91%
“…Upon lobe initiation, expansion at the lobe region may be isotropic, whereas expansion at the neck region is much reduced and primarily parallel to the tangent of the lobe as suggested by the displacement of fiducial markers (Armour et al, 2015). During lobe expansion, the periclinal wall in the lobe seems to undergo anisotropic expansion as reported by Elsner et al (2018), likely promoted by the transverse alignment of cellulose microfibrils at the base of the lobe perpendicular to its long axis (Sampathkumar et al, 2014;Bidhendi et al, 2019).…”
Section: Discussionmentioning
confidence: 87%
“…This arrangement of cellulose microfibrils at the neck region is thought to allow the wall to expand perpendicularly to the direction of the microfibrils and, thus, initiate waviness (Panteris and Galatis, 2005;Szymanski, 2014). At the lobe region of the periclinal wall, two configurations of cellulose microfibrils are suggested: A net-like configuration that allows isotropic expansion of the lobe region (Armour et al, 2015), and an arrangement parallel to the tangent of the lobe tip that allows anisotropic expansion toward the long axis of the lobe (Szymanski, 2014;Elsner et al, 2018). A recent study showed that treatment with cellulase alters Arabidopsis pavement cell shape, but does not prevent the generation of waviness (Higaki et al, 2017).…”
mentioning
confidence: 99%
“…The subcellular growth patterns associated with lobe initiation are not known. In lobed cells, the growth of periclinal walls is heterogeneous and anisotropic, with maximal extension usually occurring in the direction along the lobe axis (Elsner et al, 2018). The microtubule arrangement in pavement cells is also highly variable in space and time.…”
mentioning
confidence: 99%